Perbedaan dan pengaruh kredibilitas selebgram terhadap niat beli - Rudy Sondang Sinaga (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of celebrity credibility on consumer purchase intentions at Cafe Suoklat Surabaya. The indicators of Celebgram credibility are attractiveness, trustworthiness, and expertise. The combination of these three indicators is expected to increase the purchase intention of consumers visiting Cafe Suoklat. There are two celebgrams that will be chosen to promote the Cafe's food and beverage products through Instagram. The first is Vicky Yuwono and the second is Putri Kenasti. Data was obtained by distributing questionnaires to 100 respondents, 50 men and 50 women using purposive sampling method. Furthermore, the test was carried out using the different test method and multiple linear regression. The results showed that there was no difference in credibility between Vicky Yuwono and Putri Kenasti. Attractiveness and trustworthiness variables have a significant effect on purchase intention, except that the expertise variable does not significantly affect purchase intention.